(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wood is a raw material in short supply both in Bulgaria and worldwide. In Bulgaria, vine twigs are widespread lignocellulosic waste from agricultural production. In this study, the effect of inclusion of vine fibres in the composition of fibreboards on their properties is presented. Vine fibres were obtained by means of defibration with a defibrator laboratory mill. For the purpose of the study, fibreboards were produced under laboratory conditions with inclusion of vine fibres at a content from zero to twenty percent in increments of five percent. The main physical and mechanical properties of the boards were determined. On this basis, analysis was made and respective conclusions were drawn.